Polarimetric sensitivity of light-absorbing carbonaceous aerosols over ocean: A theoretical assessment. (September 2021) - Zhang, Chenchong; Heinson, William R.; Garay, Michael J.; Kalashnikova, Olga; Chakrabarty, Rajan K.
Highlights: Successive order of scattering (SOS) simulation of radiance and polarimetry factors for atmospheric carbonaceous aerosol. Simulations performed at wavelengths corresponding to NASA's AirMSPI's polarimetric bands. Compared to black carbon aerosol, the radiance- and polarimetry-based reflectance factors of brown carbon aerosol are more sensitive to changes in particle size and imaginary refractive index. Degree of Linear Polarization (DoLP) is most sensitive to changes in particle imaginary refractive index below 0.4. Particle size distributions modulate the level of DoLP's sensitivity to imaginary refractive index. Abstract: Visible-light-absorbing carbonaceous aerosols within the boundary layer affect the radiance and polarization states of the radiation at the top of the atmosphere. Remote sensing from suborbital and satellite-based platforms utilizes these radiance and polarization signals to retrieve the key properties of these aerosols. Recent retrieval algorithms have shown a progressive trend toward including multi-angular and multi-spectral polarimetric measurements to produce better retrieval accuracy in comparison to those using measurements based on a single viewing angle. Here, we perform a theoretical investigation of the top of atmosphere (TOA) radiance-related reflectance factor (bidirectional reflectance factor (BRF)) and the two types of polarimetry-related factors (polarized bidirectional reflectance factor (pBRF) and the degree of linear polarization (DoLP)) for different types of atmospheric light-absorbing carbonaceous aerosols as a function of particle size distribution. We selected three polarimetric bands corresponding to those utilized by NASA's Airborne Multiangle SpectroPolarimetric Imager (AirMSPI)—near-UV (470 nm), visible (660 nm), and near-infrared (865 nm)—for our simulations which were performed over ocean surface using the successive order of scattering (SOS) algorithm coupled to a Lorenz-Mie aerosol optics model. The analysis of particle phase matrix elements indicates a close relationship between the angular dependencies of DoLP and associated phase matrix components at the shortest polarimetric band (470 nm). Using Jacobian analysis, we find that the radiance- and polarimetry-related reflectance factors of weakly light-absorbing aerosols, such as brown carbon, are more sensitive to changes in particle size and imaginary refractive index in comparison with those of black carbon, which is strongly light-absorbing. Our results suggest that the DoLP data could be used by future retrieval algorithms for reliably estimating microphysical properties of absorbing carbonaceous aerosols with imaginary refractive index less than 0.4.